STRATEGI KOMUNIKASI GURU MEMOTIVASI PESERTA DIDIK DALAM MENINGKATKAN PRESTASI BELAJAR - Hairuddin Cikka (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
Motivation is something that is very important for someone in doing an activity. Motivating learning motivation can encourage optimal learning achievement. Motivation has a very important role in individual activities. Motivation needs for individual activities to produce effective results, there is a need for strong motivation and for this reason efforts are needed to generate motivation. Many teachers feel that their job is only to teach, not to motivate students. When in the classroom the teacher solely conveys the contents of the lesson to the students, in terms of conveying the lesson where students do not feel attracted by the lesson which is less favorable. Students need to get motivated. A student who has motivation will be able to learn more and faster than those who lack motivation Teacher communication with students in face-to-face activities in the teaching and learning process can be done, both individually or in groups, in the form of verbal and non-verbal, and assisted with media and learning resources. The teacher provides information, messages, ideas to students with the intention of students actively participating well in learning so that the core of the learning process can be achieved to the maximum level